Oxidative Stability, Microbial Safety, and Sensory Properties of Flaxseed (Linum usitatissimum L.) Oil Infused with Spices and Herbs - Dyana Odeh; Klara Kraljić; Andrea Benussi Skukan; Dubravka Škevin (Antioxidants, 2021)
In our study, we assessed whether the addition of basil, fennel, oregano, rosemary, and chili can improve oxidative stability and sensory properties of flaxseed oil (FO) during 180 days of storage or induce oil contamination by microorganisms. Results showed that addition of spices and herbs in FO affected the hydrolytic changes, but far less than 2% of free fatty acids after storage, which was in line with regulations. Further, the addition of spices and herbs in FO decreased peroxide value (even up to 68.7% in FO with oregano) vs. FO whose value increased during storage, indicating increased oxidative stability and prolongation of shelf life of infused oils. The antioxidant activity of the infused oils ranged from 56.40% to 97.66%. In addition, the phenol content was higher in all infused oils (6.81–22.92 mg/kg) vs. FO (5.44 mg/kg), indicating that herbs and spices could scavenge free radicals and inhibit lipid peroxidation, while sensory analysts showed that FO infused with chili had the lowest bitterness intensity. According to the presence of certain microorganisms, results highlighted the need to develop new methods for inactivating microorganisms that would not only provide a microbial safety, but also preserve the beneficial properties of the oils/products.